A metabolic interplay coordinated by HLX regulates myeloid differentiation and AML through partly overlapping pathways - Indre Piragyte (Nature Portfolio, 2018)
HLX transcription factor regulates haematopoietic stem and progenitor cell (HSPC) differentiation and is overexpressed in acute myeloid leukemia. Here the authors show that HLX overexpression leads to myeloid differentiation block in zebrafish and human HSPCs by direct regulation of metabolic pathways.